Leksykalne wykładniki emocji pozytywnych w tekście polskim w porównaniu z rosyjskim przekładem - Rudyk, Anna (Studia Rossica Posnaniensia, 2023)
This article analyses Polish nouns denoting selected positive emotional states in comparison to their equivalents in the Russian text. The factual material was taken from Katarzyna Kołczewska’s book entitled Kto, jak nie ja? and its translation into Russian, and includes sentences containing the above-mentioned nouns and their equivalents from the target text. The conducted analysis allows us to state that the nouns denoting emotions recorded in translation dictionaries, despite the presence of exact equivalents, are translated by means of lexemes modifying their meaning both in the quantitative aspect (by using lexemes indicating emotional states of higher or lower intensity), as well as in the qualitative aspect. In addition, the emotional meaning of selected nouns is conveyed in the target text by means of words referring to other parts of speech, often co-occurring with the main dictionary equivalent. The study has shown that despite the presence of established equivalents in translation dictionaries, the meaning of nouns naming selected positive emotions is conveyed in different ways in the Russian translation text. The presented repertoire of textual equivalents is by no means complete and final. The study concludes that the repertoire remains open, and textual realizations are not always consistent with the equivalents proposed by the dictionary.